The dynamic nature of parenting practices: a qualitative enquiry of parenting adolescents during COVID-19 - Babu, Nandita; Fatima, Mehreen; Arora, Manushi (Frontiers in Psychology, 2024)
The present study aimed to explore the dynamic nature of parenting practices in the context of the COVID-19 pandemic, which provided an unusual context that disrupted the routine of individuals worldwide. For this purpose, in-depth semi-structured qualitative interviews were conducted with six heterogeneous couples parenting at least one adolescent during these times. Attride-Sterling’s thematic network analysis was utilized to analyze the interview data, from which five global themes emerged, namely, change in parenting style due to stressors, paternal versus maternal style of parenting, intergenerational transmission of parenting practices, child-centric parenting practices, positive parenting practices and evolving parent-child relationship during COVID-19. A close glance at the themes revealed the impact of stressors on the parenting behavior of children. In addition, most parents employed different parenting styles not just in different situations, but also when dealing with their different kids depending on their nature, gender, and birth order. Further, the parents also compared their parenting styles with those of their parents, and in doing so, they retained the parenting practices that they considered virtuous but altered the ones that they found punitive or strict for the present generation. The study has implications for designing preventive and therapeutic interventions to modify parenting practices that can have repercussions for children’s well-being. The limitations of the study are discussed, and future directions are laid out to extend the present findings.